Evaluation of current practices and communication surrounding sudden unexpected death in epilepsy ( SUDEP ): A survey analysis of healthcare practitioners - Katherine C. Nickels; Carly Katterman; Kelly Gwin; Carla Schad (Epilepsia Open, 2026)
Abstract Objective To characterize healthcare providers' awareness and education regarding SUDEP and their approaches to SUDEP counseling. Methods A voluntary, observational 14‐question survey was administered at the 2024 American Epilepsy Society Annual Meeting to healthcare providers who treat patients with epilepsy. The survey was designed to assess SUDEP awareness, clinical training, counseling patterns, and application of SUDEP guidelines. Results A total of 114 responses were analyzed. Most respondents were epileptologists or neurologists and completed residency or fellowship between 2010 and 2024. A substantial portion of respondents (41%) reported that SUDEP training was not provided during their residency or fellowship. Nearly all respondents were aware of SUDEP risk in epilepsy patients, and 61% reported losing a patient to SUDEP. Despite endorsement by two professional medical associations, 26% of respondents were unaware of the 2017 AAN/AES SUDEP Practice Guidelines. Although almost all respondents reported counseling patients and families about SUDEP risk, only 52% counseled all patients in accordance with the 2017 guidelines, typically at or after the second visit, if at all. Respondents most frequently selected uncontrolled seizures as the top risk factor for SUDEP, followed by >3 generalized tonic–clonic seizures (GTCS), reflecting a discrepancy with guideline recommendations identifying GTCS as the primary risk factor. However, respondents prioritized ‘targeting GTCS’ similarly to ‘seizure freedom’ as a mitigation strategy. Most respondents rated SUDEP counseling practices negatively (needs improvement or unsatisfactory), were divided on preferred education/training delivery, and reported not using available counseling resources (PAME, EF, CURE, etc.). Significance The survey responses demonstrate modifiable gaps between SUDEP counseling recommendations and clinical practice. Improving residency/fellowship training, awareness of the 2017 AAN/AES SUDEP Practice Guidelines, and use of available counseling resources may help align care with established recommendations. Plain Language Summary SUDEP, or sudden unexpected death in epilepsy, is when a person with epilepsy dies suddenly and without another clear cause. This survey of epilepsy care providers asked about SUDEP awareness and how providers discuss SUDEP risk with patients and caregivers. Formal SUDEP education is inconsistent during training, and 26% were unaware of guidelines that help providers discuss SUDEP risk. Counseling is recommended for all patients and caregivers, but just over half of providers do so. Many also did not realize that generalized tonic–clonic seizures are the main risk factor. Increased SUDEP education and improved guideline awareness may improve SUDEP counseling.